Low-cost capillary electrophoresis instrumentation for assessment of rain water ionic composition - Sandak, Jakub (Array, 2019)
The objective of this Short Term Scientific Mission was to test the suitability of capillary electrophoresis for determination of rain water chemical composition. The fully functional, open-hardware, low-cost instrument was assembled and tested. An original protocol for determination of the chemical content of rain water was established and validated in the pilot test. Capillary electrophoresis proofed its highest suitability for the detection and quantification of ions in different samples, indicating substantial differences between clean and dirty snow waters. The hydrostatic sample injection method has been found very efficient and straightforward in manual and laboratory routines. An important deliverable of the Short Term Scientific Mission was a set of multimedia materials for the promotion of CE technique and especially low-cost CE instrumentation.